A Alemanha reunida e seus investimentos no exterior : um estudo de caso dos setores automotivo, financeiro e químico-farmacêutico, em nível mundial e no Brasil - Pereira, Paulo Roberto Pfeil Gomes (2007)
After the reunification, in October 3rd 1990, Germany has been strengthened its position among the richest nations in the world. At the same time, its power of influence and its participation in the global geo-political stake has been increased in the last few years. It's gross national product (GNP), based on 1996, was the third one in the world, just after the USA and Japan. However, its GNP per capita is the second bigger, behind Japan's only. Among the "emergent countries" Brazil is the first place of destination for the German investments abroad. At a worldwide level Brazil occupies the eleventh position, before important countries like Canada or Japan. Brazil is also one of the thirty most important partners of Germany in commercial exchanges. Within this context of the importance of the relationship between these two countries, this work main proposal is to qualitatively evaluate the motivations that lead the taking of decision of the German investors in the world as well as in Brazil. To achieve this task a research has been done in Germany, between January and April 1998, involving 44 enterprises and institutions belonging to three areas of economy - automobile industry, banking and chemical-pharmaceutical industry. The corporations of the automobile and chemical -pharmaceutical areas are listed among the 500 biggest of the German economy. The ones of the banking area are among the 50 biggest. The theoretic basic reference for this present work is the well known Michael Porter's The Competitive Advantage of Nations (Porter, 1993). Many of the German behavioral characteristics pointed by Porter are present in the results and the conclusions of this research. For the main objective - searching the process used for taking the decisions by the German investors at a worldwide level - we have mainly investigated the agents that motivated the German corporations involved in external investments; the definition of the concept of "stable economy" by its directors and executives; the existence and important - or not - of a governmental strategy of encouragement for these corporations to invest abroad; and the economic and financial indicators used for this kind of decision. For the specific objective - the behavior of the German capital in which says respect to Brazil - we have mainly studied the enterprise's interest for new investments in the country and their strategy for the next 5 years. We also have made a comparative analysis of the "country-risk" between Brazil and a representative group of eight countries, trying to check the influence of the late 1997 Asian crisis. Besides that, we have investigated the reasons for the reduced participation of German capital in the process of selling of the Brazilian public corporations. The conclusion of this work becomes an important means for the fitting up of portfolio país1 for long term capital goods. We suggest the formulation of different policies to attract foreign investment: short, medium and long term - in order to protect Brazilian economy from variations and crisis of the global financial stock markets. This work still intend to suggest deeper studies about the destination and the effects of the direct investments in the country "vis-a-vis" to the extension of its productive capacity and to the creation of jobs, and, finally, to the activity of the foreign corporations on Brazilian banking, prompting a stronger control on the banking mergers.